Jamshedpur riots : the truth unmasked - Jethmalani, Ram, 1923-; Bakht, Sikander; Vajpayee, Atal Bihari, 1926- (Bharatiya Janata Party, 1981)
On the Hindu-Muslim communal riots in Jamshedpur, Bihar, 1979.